The Role of Auditor Reputation as a Moderator of the Effect of Tax Aggressiveness and Public Ownership on Auditor switching Decisions - Fitria, Salsabiela Nur; Ida Nur Aeni (Atestasi : Jurnal Ilmiah Akuntansi, 2025)
Purpose: This study aims to examine tax aggressiveness and public ownership on auditor switching with auditor reputation as a moderating variable. Research Design and Methodology: The sampling technique used was purposive sampling and obtained 41 companies with a research period of 4 years so that the final amount obtained was 101 sample data. The analysis method uses logistic regression with the help of SPSS software. Findings and Discussion: The results showed that tax aggressiveness has a significant effect on auditor switching while public ownership has no significant effect on auditor switching. Auditor reputation strengthens the influence of tax aggressiveness and public ownership on auditor switching. Implications: This study contributes to the literature on auditor switching and provides practical implications for management, investors, and regulators in understanding the dynamics of auditor switching.